Death of a 29-Year-Old Male from Undifferentiated Sepsis - Kathryn A. Trebuss; Samantha Buttemer; Jeffrey S. Wilkinson; Josie Xu; John P. Rossiter; Kieran M. Moore (Canadian Journal of Infectious Diseases and Medical Microbiology)
Tumour necrosis factor alpha inhibitors, such as infliximab, and other biologic agents are associated with increased risk of opportunistic infection, including tuberculosis. Tuberculosis infections associated with infliximab tend to present atypically and can be difficult to diagnose, as they are more likely to manifest as extrapulmonary or disseminated disease. The authors report a case involving a 29-year-old male patient who died following 16 days of treatment for undifferentiated sepsis and who was found on autopsy to have widespread disseminated tuberculosis. Prior to the onset of illness, the patient had received infliximab for the treatment of Crohn’s disease. Following discussion of the case, the authors review the definition of adverse events, provide a root cause analysis of the cognitive errors and breakdowns in the health care system that contributed to the reported outcome, and identify opportunities to address these breakdowns and improve patient safety measures for future cases.